All-oral ixazomib, cyclophosphamide, and dexamethasone for transplant-ineligible patients with newly diagnosed multiple myeloma. (January 2019) - Dimopoulos, Meletios A.; Grosicki, Sebastian; Jędrzejczak, Wiesław W.; Nahi, Hareth; Gruber, Astrid; Hansson, Markus; Gupta, Neeraj; Byrne, Catriona; Labotka, Richard; Teng, Zhaoyang; Yang, Huyuan; Grzasko, Norbert; et al.
Abstract: Background: Novel efficacious treatments with long-term tolerability are needed for transplant-ineligible, newly diagnosed multiple myeloma (NDMM) patients. This phase 2 study evaluated the safety and efficacy of all-oral ixazomib-cyclophosphamide-dexamethasone (ICd) followed by single-agent ixazomib maintenance. Patients and methods: Patients were randomised (1:1) to receive 4.0 mg of ixazomib,  300 (Arm A) or 400 (Arm B) mg/m 2 of cyclophosphamide (days 1, 8, and 15), and 40 mg of dexamethasone (days 1, 8, 15, and 22) as induction (up to 13 × 28-day cycles), followed by single-agent ixazomib maintenance (28-day cycles) until progressive disease, death,  or unacceptable toxicity. Primary end-point was complete response (CR) + very good partial response (VGPR) rate for ICd induction. Results: Seventy patients were enrolled (n = 36 Arm A; n = 34 Arm B); median age was 73 years (range, 61–87). At data cut-off, 66% of patients had completed 13 induction cycles followed by ixazomib maintenance. Median overall treatment duration was 19 cycles (range, 1–29); 21% of patients discontinued treatment during induction and 3% during maintenance due to adverse events (AEs). During induction, among 67 response-evaluable patients, CR+VGPR rate was 25%, and overall response rate (ORR) was 73%. Including the maintenance phase, CR+VGPR rate was 33%, and ORR was 76%. Median progression-free survival was 23.5 months (median follow-up: 26.1 months). The most common all-grade AE was neutropenia (31%). Grade ≥3 AEs were reported by 73% of patients. Five on-study deaths occurred (not treatment-related). Conclusions: ICd treatment followed by ixazomib maintenance is tolerable and active in elderly, transplant-ineligible NDMM patients. Trial registration number: NCT02046070. Highlights: Oral ixazomib-cyclophosphamide-dexamethasone (ICd) induction followed by ixazomib maintenance is active and well tolerated. The regimen is active and tolerable in elderly, autologous stem cell transplantation-ineligible, newly diagnosed multiple myeloma (NDMM) patients. Median progression-free survival was ∼2 years, similar to that seen with the VMP standard-of-care regimen. ICd fulfils a need for non-immunomodulatory drug-containing regimens for NDMM. The regimen also meets the need for proteasome inhibitor-based maintenance therapy.